Frequency of extramedullary plasmacytomas in canines and felines diagnosed in the histopathology laboratory of the Universidad Nacional Mayor de San Marcos (period 2006-2016) - Mariño V., Paulo (2021)
The aim of this study was to determine the frequency of extramedullary plasmacytomas (EMPs) in canines and felines diagnosed in the Histopathology Laboratory of Universidad Nacional Mayor de San Marcos in the period 2006-2016. Records of histopathological diagnosis related to neoplasms were located (n=1758), of which 1703 corresponded to canines and 55 to felines. Of these, 110 (6.5%) and 8 (14.5%) were EMPs in canines and felines, respectively. The frequency of EMPs was determined with respect to the species (canine/feline), sex (male/female), age (<2, ˃2-˂7,> 7 for canines, and <1, ˃1-˂7, > 7 for cats) and breed. A frequency of EMPs of 6.5% was found in canines and 14.5% for felines in relation to the total neoplasms. Likewise, it occurred in 65 and 63% male canines and felines, respectively. Regarding age, the most affected age group in canines was >7 years, whereas in cats it appeared from one year of age. The highest frequency occurred in purebreds in canines (71%) and in mestizos in cats (88%).